Systematic Literatur Review Perkembangan Pembelajaran Gamifikasi dalam Pembelajaran Ekonomi - Saady, Farma Ladia; Suryadi, Edi; Machmud, Amir (Jurnal Pendidikan Ekonomi Undiksha, 2024)
Gamification has emerged as an approach that can increase student engagement and motivation in economics learning. The aim of this research is to conduct a systematic review of existing literature regarding the development of gamification in economic learning and then obtain a distribution for 2020-2024. The data collection technique is carried out by downloading files on the Scopus database to see trends in publications with the largest number, number of documents, ranking classifications of institutions or universities, journals and documents, as well as the use of shared keywords. The method used is bibliometric analysis. A total of 32 documents were collected through the Scopus database and then combined into one file in ris format and entered into the VOSviewer application to obtain network visualization and overlay visualization. The research results show that the trend of publications related to gamification learning in economics learning has increased from year to year. The largest number of documents is in "Springer Proceedings in Business and Economics" with four documents. A publication with the title "The effects of a gamified project based on historical thinking on the academic performance of primary school children" written by Martinez et al. (2021) with a total of 14 citations. Student is the most widely used gamification keyword along with 5 cooccurrences. Based on the keywords visualized, there are several keywords that are trending. Research focuses on gamification learning in economic learning, namely students, e-learning, economic disciplines, higher education, education, experiential learning, online learning, flipped classroom, innovation.